MEMETIC DIALECTICS AND AGENT HABITUS THROUGH COMMODIFICATION AND REALITY CONSTRUCTION IN PROVERTY PORN CONTENT VIDEOS ON SOCIAL MEDIA - A. Yudo Triartanto,; Tuty Mutiah,; Adhi Dharma Suriyanto, (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
This research focuses on videos containing proverty porn or poverty pornography found on social media platforms like YouTube and TikTok. This means that poor people are portrayed in YouTube and TikTok videos as content to be exploited for financial gain. The phenomenon of proverty porn presented on social media, in this context, is related to agents a term Pierre Bourdieu uses for actors as content creators of video content. Therefore, this research utilizes the concepts and theories of memetics, habitus, commodification, and the construction of media reality. The use of memetics and habitus concepts reflects the dialectic that occurs within agents or content creators in creating video content. The dialectic within agents becomes significant when habits (habitus) and memetics (imitation) engage in a dialectical process or have a reciprocal relationship. The results of the study show that repeated habits are also repeated imitations to create video content continuously simply because they can become commodities. All incidents of poverty that occur are constructed as reality in the media.